Effects of a Chinese Herbal Medicine, Guan-Jen-Huang (Aeginetia indica Linn.), on Renal Cancer Cell Growth and Metastasis. (16th August 2011) - Liu, Yu-Huei; Li, Meng-Luen; Hsu, Meng-Yu; Pang, Ya-Yueh; Chen, I-Ling; Chen, Ching-Kuei; Tang, Sai-Wen; Lin, Hsuan-Yuan; Lin, Jung-Yaw
Abstract : Aeginetia indica Linn. (Guan-Jen-Huang, GJH), a traditional Chinese herb, has the potential to be an immunomodulatory agent. The purpose of this study was to explore the effect of GJH in the treatment of renal cancer. Concentration-effect curves for the influence of GJH on cellular proliferation showed a biphasic shape. Besides, GJH had a synergistic effect on cytotoxicity when combined with 5-fluorouracil (5-FU)which may be due to the alternation of the chemotherapeutic agent resistance-related genes and due to the synergistic effects on apoptosis. In addition, treatment with GJH extract markedly reduced 786-O cell adherence to human umbilical vein endothelial cells (HUVECs) and decreased 786-O cell migration and invasion. In a xenograft animal model, GJH extract had an inhibitory effect on tumor cell-induced metastasis. Moreover, western blot analysis showed that the expression of intercellular adhesion molecule-1 (ICAM-1) in 786-O cells was significantly decreased by treatment with GJH extract through inactivation of nuclear factor- κ B (NF– κ B). These results suggest that GJH extract has a synergistic effect on apoptosis induced by chemotherapeutic agents and an inhibitory effect on cell adhesion, migration, and invasion, providing evidence for the use of water-based extracts of GJH as novel alternative therapeutic agents in the treatment of human renal cancer.